Potensi Isolat Bakteri Pelarut Fosfat Asal Tanah Gambut Riau dalam Memproduksi Hormon Indole Acetic Acid (IAA) dan Pengaruhnya Terhadap Perkecambahan Benih Cabai Merah (Capsicum annuum L.) - Dwi Wahyuni; Tetty Marta Linda; Wahyu Lestari (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
Indole Acetic Acid (IAA) is a group of auxin hormone role in regulating the growth and development. Bacterial isolated from peat soils of Riau known activity in dissolving the phosphate in the Pikovskaya medium and Red-Yellow Podzolic Soil. The purpose of this study was to test isolates from peat soils of Riau in producing IAA hormone and its effects on the germination seeds of red pepper. The results showed that the production ofIAA in Nutrient Broth (NB) not signifficant to all treatments, but tends to be highest on GGO6 that is equal to 9.72 ± 5.91 ppm. The addition of L-tryptophan in the media NB indicated that GGO2 (24.51 ± 5.53 ppm) and GGO6 (19.61 ± 1.80 ppm) significantly to GGO4 (11.33 ± 4.12 ppm). Soaking seeds of red pepper on each bacteria tend to increase the rate of seed germination. Shoot length on GGO5 not different from GGO1, GGO2 and GGO3, but significantly different with the GGO4, GGO6 and control. While GGO1 and GGO3 also significantly different with control. Root length for all treatments significantly different with the control except GGO4.